Development of ca-alginate-chitosan capsules for encapsulation and controlled release of imidacloprid as larvaecide delivery system - Lim, Gim Pao (School of Bioprocess Engineering, 2018)
The research objectives are to investigate the effect of encapsulation solution formulation and process variables on the size and shape of the capsules produced using co-axial air extrusion system; to characterize Ca-alginate-chitosan capsules, unloaded or loaded with imidacloprid using SEM, FTIR, DSC, TGA, and XRD; to evaluate effects of varying concentration of chitosan, alginate, pH, size and temperature on the swelling capability and in vitro release kinetic of imidacloprid loaded Ca-alginate-chitosan capsules; to examine the best fit kinetic models of imidacloprid release kinetics using kinetic equations and to propose the release mechanism of imidacloprid from Ca-alginate-chitosan capsules; to evaluate the efficacy and effective duration of imidacloprid loaded Ca-alginate-chitosan capsules with different diameter against a commercial larvaecide through in vivo and field testing experience as a larvaecide delivery system.